Ambient Medicine®: telematic musical feedback in hypertension therapy. (1st June 2016) - Friedrich, Petra; Wolf, Bernhard
Abstract : Background : Acoustic signals can modulate metabolic and central nervous functions and evoke physiological effects within humans. Especially, the anti-hypertensive effect of certain iterative sound patterns as possible intervention in essential hypertension, which originates in many cases from stress, is examined with COMES ®, the Cognitive Medical System based on telemedicine. Methods : This contribution describes the structure, the mode of operation and introduces the detailed results of the prospective observational study ( N  = 20) of musical feedback in hypertension therapy. Results : It is shown that the music used for intervention can decrease blood pressure significantly ( t -test). The reduction averages −2.57 mmHg ( p   = 0.013) RRsys, −1.54 mmHg ( p  = 0.003) RRdia. This is comparable with pharmaceutical interventions. Discussion : COMES offers a great number of application options in diagnostics and therapy including an automatic intervention channel. It is possible to gather authentic data patterns in the patient's personal environment and thus to obtain an immediate, realistic impression of arbitrary intervention structures. Therapists get further instruments to involve their patients actively into the therapy process at home. The measurement of various physiological parameters allows both patient and therapist a direct feedback on the efficacy of therapeutic intervention or relaxation exercises.